Galvanic Displacement of Gallium Arsenide Surface: A Simple and Low-Cost Method to Deposit Metal Nanoparticles and Films - Ngoc Duy Pham; Seok Ju Park; Jun Pil Lee; Ilwhan Oh (Journal of Chemistry)
Herein, we report galvanic displacement of metal nanoparticles and films onto single-crystalline GaAs (100) substrates, a simple and cost-effective method to fabricate highly controlled metal/semiconductor interface. A time-resolved surface analysis of Au/GaAs system was conducted and microscopic mechanism of galvanic displacement was elucidated in detail. Quantitative temporal XPS measurements of the Au/GaAs interface showed that, initially, fast Au growth was slowed down as the deposition process proceeded. This was attributed to growing oxide layer blocking hole conduction and causing quenching of the deposition process. Addition of various inorganic acids, which function as oxide etchants, was found to enhance deposition rates by effectively removing surface oxide, with HF the most effective. Various precious metals, such as Pt and Ag, could be deposited onto GaAs through galvanic displacement, which demonstrates the versatility of the method.